Clinicodemographic Profile and Outcome of Patients with Symptomatic Meckel’s Diverticulum: Preliminary Findings - Joshi, Pravin; Belbase, Narayan; Mishra, Rohit Kumar; Karki, Mukesh; Das, Lalit Kumar (Journal of College of Medical Sciences-Nepal, 2020)
Background: Meckel's diverticulum is the commonest gastrointestinal congenital anomaly. Though most of the cases do not present clinically, they are challenging to diagnose if become symptomatic. Spectrum of clinical presentation may be different from umbilical fistula, omphalomesenteric cyst to fibrous band from diverticulum to umbilicus. Bleeding, obstruction and infection are the most common complications. Vast majority of them are detected only intra-operatively. Methods: We analyzed our patients who were intra-operatively diagnosed as symptomatic Meckel's Diverticulum. Socio-demographic profile and immediate outcome of operated patients was analyzed from patient's records. Results: Total 9 patients were operated for symptomatic Diverticulitis. All patients were diagnosed intraoperatively. Intestinal obstruction was the commonest presentation. Diverticulectomy was the most common procedure performed followed by wedge resection and segmental bowel resection. Conclusions: Symptomatic Meckel’s Diverticulum is difficult to diagnose pre-operatively. Vast majority of them are found only intra-operatively. Most of the patients do well after resection of Meckel's Diverticulum. Keywords: Meckel’s diverticulum; surgery; symptoms.